2018
DOI: 10.1002/ajh.25232
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance is an underlying mechanism of impaired glucose metabolism during nilotinib therapy

Abstract: TP and CG contributed equally to this work REFERENCES SUPPORTING INFORMATIONAdditional supporting information may be found online in the Supporting Information section at the end of the article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Molecular docking was performed to predict the binding of rosuvastatin and aspirin to the hub proteins and the targets enriched in the atherosclerosis signaling pathway. The three-dimensional structures of rosuvastatin and aspirin were obtained from the PubChem database, 8 and the three-dimensional structures of hub proteins were obtained from the RCSB Protein Data Bank (PDB) database. 9 Molecular docking simulations between rosuvastatin, aspirin and the target proteins were performed by using the AutoDock Tool (version 1.5.6) and AutoDock Vina 1.1.2 (Molecular Graphics Laboratory, Scripps Institute, 2011).…”
Section: Molecular Dockingmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular docking was performed to predict the binding of rosuvastatin and aspirin to the hub proteins and the targets enriched in the atherosclerosis signaling pathway. The three-dimensional structures of rosuvastatin and aspirin were obtained from the PubChem database, 8 and the three-dimensional structures of hub proteins were obtained from the RCSB Protein Data Bank (PDB) database. 9 Molecular docking simulations between rosuvastatin, aspirin and the target proteins were performed by using the AutoDock Tool (version 1.5.6) and AutoDock Vina 1.1.2 (Molecular Graphics Laboratory, Scripps Institute, 2011).…”
Section: Molecular Dockingmentioning
confidence: 99%
“…A total of 23.3% of patients have at least one arterial obstructive event, which suggests that cardiovascular toxicity remains a concern. Nilotinib (NILO) can cause accelerated atherosclerosis and arterial thrombotic events (myocardial ischemia, stroke, and peripheral artery obstructive disease), hyperglycemia and hyperlipidemia ( 7 , 8 ). The risk increases with the nilotinib administration duration ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 43 ] A prospective study on patients with CML who were treated with nilotinib for 12 months showed a significant increase in blood glucose levels. [ 44 ]…”
Section: Type 2 Diabetesmentioning
confidence: 99%
“…Interestingly, treatment of high-fat diet mice with nilotinib increases insulin sensitivity and decreases fat mass,[ 45 ] which contradicts the clinical data of the adverse effects of nilotinib on glucose impairment. One possible explanation is that clinical observations[ 42 , 44 ] have focused on insulin secretion rather than insulin action. Another probable reason is that nilotinib may have off-target effects that may include dual effects of insulin.…”
Section: Type 2 Diabetesmentioning
confidence: 99%
“…Such events are clearly influenced by individual background, patients already at high or very high cardiovascular disease (CVD) risk being the most vulnerable [28], [21••]. Nilotinib also impairs glucose and cholesterol homeostasis through mechanisms that are not completely understood [29] [30]. These parameters need to be tightly monitored and controlled throughout treatment as diabetes and dyslipidemia are well-known risk factors for CVD.…”
Section: Safety Of First-line Tkis and Patient-related Factorsmentioning
confidence: 99%